Tracking of health-related physical fitness in adolescent girls: a 3-year follow-up study - Kasović, Mario; Oreški, Ana; Vespalec, Tomaš; Jenčíková, Kateřina; Štefan, Lovro (BMC pediatrics, 2022)
BACKGROUND: Evidence has shown that higher levels of physical fitness (PF) in youth have beneficial effects on adult health-related outcomes. However, the tracking of separate PF components during adolescence has been less studied. Since PF often starts to rapidly decline during adolescence, it is necessary to provide information regarding critical time-point for interventions. This study aimed to analyze the extent of tracking the components of PF through PF tests. METHODS: In this longitudinal study, we recruited 240 adolescent girls with recoded data at 2 time-points (15 y and 17 y). PF included body composition (fat mass), explosive power of lower extremities (standing broad jump), muscle endurance of the trunk (sit-ups in 60 s), flexibility (sit-and-reach test), muscle endurance of lower extremities (squats in 60 s), aerobic endurance (the 800 m run test) and speed endurance (the 400 m run test). Tracking coefficients were calculated using generalized estimating equations. Tertiles (high, moderate and low) were calculated for each fitness component. RESULTS: The highest tracking coefficients between the two time-points were found for explosive power of lower extremities (β = 0.98), followed by flexibility (β = 0.89), body composition (β = 0.88), speed endurance (β = 0.86), aerobic endurance (β = 0.75), muscle endurance of lower extremities (β = 0.65), and muscle endurance of the trunk (β = 0.51). Tertile ratings remained stable across the two time-points. CONCLUSIONS: Moderate to high tracking of PF in adolescent girls suggests that interventions aiming to increase the level of PF should probably begin in early adolescence.
Keywords: Body Composition; tělesná výkonnost; Humans; složení těla; Youth; Exercise; Female; mladiství; následné studie; Secondary school; ženské pohlaví; Follow-Up Studies; Performance; Adult; Longitudinal Studies; Stability; cvičení; Adolescent; longitudinální studie; dospělí; lidé; Physical Fitness; Generalized estimating equations